Minimum Profitability Ruling a Boon or Bane? Some Lessons from China - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
China’s Securities Regulatory Commission (CSRC) stands out in its approach to tighten restrictions for listed companies wanting to initiate rights issues or seasoned equity offerings (SEOs). The country’s experience, relevant to other emerging markets, is the subject of a research paper published recently in the International Journal of Accounting, co-authored by Kevin C.W. Chen, accounting professor at the Hong Kong University of Science and Technology and Singapore Management University accounting professor Jiwei Wang. --------------------------------------------------------------------------------